The Underutilized Rehabilitation Policy: Why Local Wisdom Matters in Developing Narcotics Prisoners - Mulyadi Alrianto Tajuddin; Gunarto Gunarto; Aris Setiyono; Ali Salem Al-Hammouri; Muhammad fitri Adhy (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
The persistently high rate of recidivism among narcotics offenders demonstrates that rehabilitation policies within the Indonesian correctional system have not been optimally implemented and continue to produce limited outcomes. Current rehabilitation practices predominantly adopt standardized and administratively driven models that marginalize the social, cultural, and moral dimensions inherent in drug dependency. As a result, these models fail to respond adequately to the complex and context-specific challenges encountered by narcotics prisoners, particularly within Indonesia’s socio-cultural diversity. This study proposes an alternative rehabilitation framework that integrates local wisdom values rooted in Pancasila to construct a more contextual, humane, and socially responsive strategy for reducing recidivism. Using a socio-legal research design and descriptive qualitative methods, the study systematically examines statutory regulations, academic discourse, and living customary norms, with empirical attention directed toward community-based practices in Papua. The analysis indicates that, first, the dominance of standardized and administratively oriented rehabilitation models within the Indonesian correctional system limits their effectiveness in addressing the socio-cultural and moral dimensions of narcotics dependency, thereby contributing to persistent recidivism. Second, local wisdom values grounded in Pancasila, particularly customary deliberation, collective responsibility, and community-based social rehabilitation, function as effective normative mechanisms for fostering moral awareness, personal accountability, and social reintegration among narcotics prisoners. Third, the systematic integration of these local values throughout the rehabilitation process, from sentencing to post-release reintegration, enhances both the practical effectiveness and the substantive legitimacy of correctional policies, reflecting the realization of justice that is contextual, humane, and culturally embedded.